Evaluation of Drought Tolerance Indices and Physiological Traits in Cultivated and Wild Barley - mohammad barati (Tulīd va Farāvarī-i Maḥṣūlāt-i Zirā̒ī va Bāghī, 2017)
Drought stress is one the most limiting factors for crop production worldwide. The wide ecological and environmental dispersion of crop wild relatives, generates a high potential of their adaptive diversity to abiotic stresses such as drought. In this study 21 (including 10 cultivated and 11 wild barley (Hordeumvulgaressp. spontaneum))genotypes were evaluated under three soil water conditions for grain yield, drought tolerance indices (STI and YSI) and some physiological traits during two growing seasons(2012-2013 and 2013-12014). High genetic variation was observed for grain yield and STI and YSI indices between and within cultivated and wild barley groups of genotypes. Differences were also observed between the genotypes for physiological traits. Different responses of the genotypes to different levels of drought stress were also observed for all of the measured traits. The high-yielding varieties were more tolerant based on STI index, but the average of yield stability under stressed conditions (YSI) was significantly higher in the wild barley group of genotypes comparing to cultivated ones, indicating a high level of drought tolerance in wild genotypes. Among physiological traits, significant differences were observed for relative water content and proline content between cultivated and wild barley genotypes, showing the importance of these two traits in different response of the two genotypic groups to drought stress. The STI and YSI indices identified the most drought tolerant genotypes at different soil moisture levels. The tolerant genotypes were mostly belonged to wild barley. These genotypes can be used in breeding programs by crossing them with high-yielding varieties such as Reihan 03 for increasing drought tolerance of cultivated barley.